Recycling of silicon-based solar panels - Tang, Wei Ye (Nanyang Technological University, 2023)
Climate changes and the increase in global warming are two of the biggest challenges our planet is facing today. These have sparked a hunt for alternative energy sources, and one of the potential viable options is photovoltaics (PV). PV is known to be safe, clean, and does not emit harmful gases during the energy generation process. Since then, the PV sector has seen sharp growth as many converts from conventional energy sources to PV. The growth has been further accelerated by government initiatives to promote PV as an alternative energy source. It is crucial that effective waste management for end-of-life (EoL) panels is in place to handle the high anticipated amount of waste in the coming years due to the growing number of installations and the warrantied lifespan of only 25–30 years. The volume of decommissioned panels is predicted to be even higher due to early decommission to replace with more efficient PV panels. A typical silicon-based solar panel comprises of a variety of raw materials such as silicon, aluminium, silver, copper, lead and tin, and the extraction of these metals will allow us to reuse and repurpose them. Strong acids and/or bases like nitric acid (HNO3), hydrofluoric acid (HF), and sodium hydroxide (NaOH) have often been employed in the metal extraction stages. Noxious gases such as nitrogen oxides (NOx) can be produced during the chemical extraction when HNO3 is utilised. On the other hand, HF and NaOH are highly corrosive and can harm the environment if not handled properly before discharge. As a result, a more ecologically friendly leaching strategy is required. This project focuses on exploring the use of organic acids and oxidizing agents to replace the harmful inorganic acids for the metal extraction process. In this study, we investigate the feasibility of employing citric acid and acetic acid to stepwise dissolve metals present in the PV. Temperature, solid-to-liquid (S/L) ratio and addition of hydrogen peroxide (H2O2) are variable parameters studied to understand the effect on the metal leaching efficiencies.